2020
DOI: 10.1093/cid/ciaa227
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of First Case of COVID-19 in Canada: Lessons Applied From SARS-CoV-1

Abstract: Abstract We report diagnosis and management of the first laboratory-confirmed case of coronavirus disease 2019 (COVID-19) hospitalized in Toronto, Canada. No healthcare-associated transmission occurred. In the face of a potential pandemic of COVID-19, we suggest sustainable and scalable control measures developed based on lessons learned from severe acute respiratory syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
101
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 11 publications
0
101
0
Order By: Relevance
“…A case report describing the first case of Canada showed that the patient had symptoms of hemoptysis on days 2 through 6 along with fever and non-productive cough on presentation [24]. Lillie et al presented a case where symptom onset started with fever, which then progressed to sore throat and dry cough followed by diffuse myalgia.…”
Section: Clinical Signs/symptomsmentioning
confidence: 99%
“…A case report describing the first case of Canada showed that the patient had symptoms of hemoptysis on days 2 through 6 along with fever and non-productive cough on presentation [24]. Lillie et al presented a case where symptom onset started with fever, which then progressed to sore throat and dry cough followed by diffuse myalgia.…”
Section: Clinical Signs/symptomsmentioning
confidence: 99%
“…1 Although there are numerous case series and commentaries regarding the natural course of the pandemic, there is a relative paucity of data specific to the ED context. [3][4][5][6][7] Given that the number of new COVID-19 cases is likely to wax and wane in response to dynamic public health policies, it remains imperative that ED clinicians have regular, real-time and locally relevant information to inform patient care.…”
Section: Introductionmentioning
confidence: 99%
“…When assessing patients with deteriorating conditions, it has been noted that CRP is significantly raised and albumin is low(31). While no clear guidelines exist on the evaluation of response to supportive treatment, a study by Cascella et al has suggested that laboratory evaluation of samples from patients should demonstrate viral clearance prior to discharging from observation in the form of two negative respiratory tract specimens taken at least 24 hours apart(66,67).…”
mentioning
confidence: 99%